Enhancing ultra-wideband THz fingerprint sensing of unpatterned 2D carbon-based nanomaterials. (July 2021) - Ding, Shan; Ou, Jun-Yu; Du, Lianghui; Zhu, Liguo; Khan, Sayed Ali; Chen, Huanyang; Zhu, Jinfeng
Abstract: THz molecular fingerprint sensing is a promising non-destructive method to accurately detect ultra-thin carbon-based materials in the nanoscale. Due to their extremely low THz absorption, plasmonic metamaterials or all-dielectric metasurfaces have been adopted to enhance the light-matter interaction for detection. However, they cause considerable parasitic losses or complicated material processing on a patterned surface. Here, we propose a lithography-free all-dielectric sensor to enhance THz absorption via an evanescent wave, which can lead to high detecting performance by a coupled mode. In view of the molecular broadband features, we use a thickness-multiplexed scheme to boost the detection of fingerprint significantly. The enhancing factor for the minimum fluctuation of fingerprint feature points is up to 534. Our method drastically enhances the broadband fingerprint intensity of the ultra-thin nanoscale layer and make it comparable to that of a 700-times thick sample layer, measured with a regular approach. Our study paves the way for broadband THz fingerprint sensing of trace-amount analytes and will inspire many burgeoning THz detection applications on 2D or ultra-thin carbon-based nanomaterials. Graphical abstract: Image 1